All Days 2012
DOI: 10.2118/157882-ms
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Induced Chain Reactions of Heavy Petroleum Fluids—Dominant Process Variables

Abstract: Ionizing electron particles were used as an efficient means of delivering energy to heavy hydrocarbon molecules. Although heavy oil reserves are known as rich sources of energy, their contribution to the energy market has been impacted by the fact that the conventional thermal or catalytic upgrading and visbreaking methods always demand a considerable energy and money investment. Therefore, application of potential alternatives with lower operating costs and higher process throughput appears to be extremely cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Although application of ionizing particles in petroleum industry has had a rapid growth during the recent decades, quite a few works have investigated the rheological property changes that are brought about because of radiation-induced reactions. Alfi et al showed that electron-induced thermal cracking of heavy petroleum fluids results in products with lower viscosities than the thermal cracking cases.…”
Section: Introductionmentioning
confidence: 99%
“…Although application of ionizing particles in petroleum industry has had a rapid growth during the recent decades, quite a few works have investigated the rheological property changes that are brought about because of radiation-induced reactions. Alfi et al showed that electron-induced thermal cracking of heavy petroleum fluids results in products with lower viscosities than the thermal cracking cases.…”
Section: Introductionmentioning
confidence: 99%